A CONCEPTUAL STUDY ON PANCHAKARMA APPROACH IN THE MANAGEMENT OF ANKYLOSING SPONDYLITIS - D M, *Shreyas; M.Goud, Kiran.; K.N, Vinaykumar.; Deshpande, Swathi (International Journal of Ayurveda and Pharma Research, 2017)
Ankylosing spondylitis is characterized by a chronic inflammatory arthritis predominantly affecting the sacro-iliac joints and spine, which can progress to bony fusion of the spine. The onset is typically between the ages of 20-30, with male preponderance of about 3:1. The main symptoms like musculoskeletal pain, stiffness and decreased range of movements in the spine. Modern science has very limited options to treat Ankylosing spondylitis. So, the necessity of management through Ayurveda is very much essential. Various disease entities like Amavata, Gambhira Vatarakta, Asthimajjagata vata can be considered under the spectrum of Ankylosing Spondylitis. By understanding the symptoms of Ankylosing Spondylitis, the pathology pertaining to the Ankylosing Spondylitis can be considered under the Sama and Nirama avastha. A thorough differentiation of Sama and Nirama avastha of Ankylosing spondylitis (Gambhira Vatarakta) has to be done based on the same, Panchakarma procedures are to be adopted. Among various modalities of treatments, Panchakarma can be the better option to treat this condition. Hence, a conceptual study was taken up to develop an approach through Panchakarma modalities in the management of Ankylosing Spondylitis.